Impact of respect, equity, and leadership in brain health - Arshad, Faheem; Zegarra-Valdivia, Jonathan Adrian; Prioleau, Caroline; Valcour, Victor; Miller, Bruce L. (Frontiers in Neurology, 2023)
Respect is a feeling of admiration for someone. It forms one of the core values of the Global Brain Health Institute (GBHI), which strives to protect the world’s aging populations from threats to brain health. These values guide us as we advocate for reducing the global impact of dementia. By taking a values-based approach to brain health, we can drive global changes for millions of people. Respect fortifies gratitude and embraces diversity. Philosophical discussions of the ideas support the assertion that respect is crucial in everyday conversations and actions as well as in personal, social, political, and moral spheres. No one can become a leader unless they genuinely respect and care about the success of each team member. Diversity, equity, and inclusivity form the fundamental cornerstones of respect. Understanding this core value of respect will ensure altruistic behavior among the leaders that may help mitigate racism, cultural insults, gender discrimination, stigmatization, religious hatred, and, worst of all, poor leadership abilities that have been the disconcerting examples of disrespect in recent years. We present the underlying neurobiology of respect and its impact on equity and leadership.